EXPOSURE INDEX (EI) SEBAGAI ALAT OPTIMISASI PADA SISTEM RADIOGRAFI DIGITAL: IMPLEMENTASI DAN TANTANGAN BAGI RADIOGRAFER - Putu Irma Wulandari (JRI (Jurnal Radiografer Indonesia), 2023)
Background: The existence of ”exposure creep” in digital radiography systems has been debated over years, raising concern in image optimisation. Therefore, effective implementation of Exposure Index (EI) as a tool for optimisation has been stressed to address this issue. However, the concept of ”exposure creep” and Exposure Index (EI) might not be familiar to all Indonesian radiographers. This study aims to explore the current literature related to EI, including the development, current status, and challenges in its implementation. Methods: Literatures were explored in various databases using the following keywords; “Exposure Creep”, Radiation dose in Digital Radiography, Optimisation in Digital Radiography, Exposure Index, Deviation Index, etc. Only references, such as books, journal articles, and official reports in Bahasa Indonesia and English are included in this study. Results: The term “Exposure Creep” refers describe a gradual increase in exposures following the implementation of digital radiography systems. Exposure Index is used as a feedback for radiographers regarding exposures in image acquisition. However, in the beginning of its development there have been several issues, leading to confusion to users. Therefore, the development of the standardized Exposure Index (IEC 624924-1) has been proposed. This article also addresses several challenges in EI implementation and take-home points for radiographers. Conclusions: Radiographers should be familiar with the basic concept of EI in order to effectively implement it as an optimisation tool.